2020
DOI: 10.1002/ecm.1432
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and alternative stable states after desert wildfires

Abstract: Improving models of community change is a fundamental goal in ecology and has renewed importance during global change and increasing human disturbance of the biosphere. Using the Mojave Desert (southwestern United States) as a model system, invaded by nonnative plants and subject to wildfire disturbances, we examined models of resilience, alternative stable states, and convergent‐divergent trajectories for 36 yr of plant community change after 31 wildfires in communities dominated by the native shrubs Larrea t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 87 publications
(113 reference statements)
2
12
0
1
Order By: Relevance
“…The potential for divergent trajectories of change due to variation in primary forcing factors is well recognized in the broader ecological and geomorphic disturbance literature (i.e. Abella et al, 2021; Gutiérrez‐Cánovas et al, 2019; Laurance et al, 2007; Phillips, 2009) but has seldom been explicitly considered in the context of coastal dune dynamics following disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for divergent trajectories of change due to variation in primary forcing factors is well recognized in the broader ecological and geomorphic disturbance literature (i.e. Abella et al, 2021; Gutiérrez‐Cánovas et al, 2019; Laurance et al, 2007; Phillips, 2009) but has seldom been explicitly considered in the context of coastal dune dynamics following disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Fire is increasing in extent, severity, and frequency across the western United States, and forecasts suggest continued increases in wildfire for these dry ecosystems (Abatzoglou & Williams, 2016; Parks et al, 2016). Many North American desert systems historically have had relatively low fire frequency and long fire return intervals, and a range of studies have assessed the consequences of increasing fire on the aboveground plant communities of these deserts (e.g., Abella et al, 2020; Jurand & Abella, 2013; Miller et al, 2016; Pyke et al, 2010; Shryock et al, 2014). While the importance of the aboveground vegetation trajectories after fire is not to be minimized, terrestrial plants also exist in the soil seed bank and this belowground component of the plant community plays a critical role in determining a site's future plant community.…”
Section: Discussionmentioning
confidence: 99%
“…Despite our data showing no effect of burn status on densities and richness, we found that seed bank communities were different for both longer and shorter TSFs in our cold desert sites. Studies looking at aboveground vegetation have shown that recovery following fire is variable within and across dryland systems (Abella, 2009; Abella et al, 2020; Morris & Leger, 2016; West & Hassan, 1985). The lack of vegetation recovery after fire is at least in part due to the limited ability of many desert shrubs and cacti to resprout following fire (Abella, 2009; Shryock et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can have important consequences for ecosystem functioning, as the ecosystem stays in the new attraction valley -the alternative state -even if the perturbation that triggered the change has ceased. Numerous studies have demonstrated the existence of abrupt changes to alternative states in aquatic ecosystems 9,11 , terrestrial plant communities 12,13 , and the human gut microbiome in response to perturbations 14,15 . However, abrupt transitions to alterative states in soil microbial communities have so far received little attention 7 , despite their fundamental role in terrestrial ecosystems, driving key processes of organic matter decomposition, nutrient cycling, and carbon and nutrient storage 16 , which regulate ecosystem productivity.…”
mentioning
confidence: 99%